Vitamin D Status in Russian Children and Adolescents: Contribution of Genetic and Exogenous Factors - Kondratyeva, Elena I.; Zakharova, Irina N.; Ilenkova, Natalya A.; Klimov, Leonid Ya.; Petrova, Nika V.; Zodbinova, Aisa E.; Zhekaite, Elena K.; Chikunov, Vladimir V.; Dolbnya, Svetlana V.; Voronkova, Anna Yu.; Sherman, Victoria D.; Loshkova, Elena V.; et al. (Frontiers in Pediatrics, 2020)
Background: The problem of vitamin D deficiency is particularly relevant for the entire territory of Russia, since most parts of the country are located above the 42nd geographical latitude and the residents are therefore at risk of vitamin D deficiency. Different variants in the loci of the genes responsible for the synthesis, hydroxylation, and transport of vitamin D as well as VDR gene polymorphisms may also be associated with the risk of vitamin D deficiency. Methods: We conducted blood 25(OH)D level analysis in 333 healthy children and adolescents in three regions located in different geographical zones of the Russian Federation. Polymorphic variants of cytochrome and VDR genes were studied by restriction analysis. We analyzed the influence of exogenous factors on the level of 25(OH)D in children of the three study regions, as well as the relationship of the level of 25(OH)D with polymorphic variants of CYP2C9*2, CYP2C9*3, CYP2D6*4, CYP3A4, CYP3A4*1B and with BsmI, TaqI, and FokI polymorphisms of the VDR gene. Results: We found that the blood level of 25(OH)D depended on the geographical location and the number of sunny days per year. The average blood level of 25(OH)D in adolescent boys was statistically significantly lower than in girls of this age group. The level of 25(OH)D also significantly depended on the prophylactic dose of cholecalciferol administered to the subjects. In the study, it was shown that a dose of cholecalciferol ≥1,000 IU per day can achieve a normal level of 25(OH)D in healthy children. We found no statistically significant association between single-nucleotide polymorphic variants of cytochrome P450, genes the TaqI, FokI, and BsmI polymorphisms of the VDR gene and serum 25(OH)D concentration. Conclusion: Exogenous factors (time of year, place of residence, and prophylactic administration of cholecalciferol), as well as endogenous factors (age and sex), play a determining role in the development of vitamin D deficiency; in contrast to genetic factors—polymorphic variants of the genes of xenobiotic phase 1 enzymes (CYP2C9, CYP2C19, CYP2D6, and CYP3A4) and the VDR gene—which do not play such role.